KONTRIBUSI KOORDINASI MATA-TANGAN DAN KEKUATAN OTOT LENGAN TERHADAP TEMBAKAN DIBAWAH RING PADA SISWA SMA NEGERI 1 KOTABARU - Arham Syahban (STKIP Paris Barantai, 2018)
The purpose of this study was to determine the contribution of eye-hand coordination and arm muscle strength to shots under the ring in a basketball game students in SMA Negeri 1 Kotabaru.The method used in this research is descriptive research method of quantitative approach and data retrieval is done through test and measurement. The population in this study are the students of grade X SMA Negeri 1 Kotabaru which amounted to 144 students and samples taken in the study of 36 students with simple random sampling technique.The results of the analysis indicate that there is a contribution of hand-eye coordination (X1) to the shot under the ring on basketball (Y) of 12.9%. There is a contribution of arm muscle strength (X2) to the shot under the ring on basketball (Y) of 11.7%. There is a contribution of hand-eye coordination (X1) and arm muscle strength (X2) simultaneously to the shot under basket rings (Y) of 22.7%.Keywords: Hand-eye Coordination, Muscle Arm Strength, Shot under Ring on Basketball.